Investigating Changes in Chlorine and Salinity Levels of Groundwater in Firoozabad Plain and Evaluation of Comparison of Agricultural and drinkable water - ghorban vahabzadeh; hojat delavar; jamshid ghorbani; mohammad reza ashrafi (Mashhad University of Medical Sciences, 2018)
Abstract Background and Purpose Changing the quality of groundwater and saltinating of water resources are Concerning a major threat for country's agricultural development, especially in arid and semi-arid lands. Preparing maps of both Same amount maps for salinity and salts can be an important step in the proper utilization of water resources. This research was carried out in Firoozabad plain in west of Fars province to evaluate the hydrogeochemical processes affecting groundwater quality. Method Preparation of the map of the chemical parameters (isochromic) of Firoozabad plain using hydrodynamic data of wells measured in East and West of Firoozabad plain. Preparation of similar maps using Shooler and Wilcox methods to produce coincidence lines it placed. Findings Based on the maps of the chemical parameters in the studied areas and the diagrams of the changes and classification of the data based on the Schuler and Wilcox diagrams, the irrigation water classification according to Wilcox's diagram in 2004 and 2011 showed a decline trend in agricultural quality. Based on the results of the classification of drinking water, there were generally no significant changes in drinking quality except in 2011. Conclusion The amount of chlorine and electrical conductivity parameters in the west and east of the Firoozabad plain increased from north and northwest to the center and eastern plain from east to center, respectively, in the east and west of the plain, the highest values ​​were observed. Also, the results showed that the groundwater of the area based on the Schuler diagram was classified into three classes: good, acceptable and moderate, and quality, for use in agriculture in 2011 in C3S1, C1S1, C2S1 C3S2, C3S4, C3S3 and in the first period, 2004, in C3S1, C1S1, and C2S1 classes. The irrigation water classification according to Wilcox, in terms of 2004 and 2010, indicates a decrease in agricultural quality. The results of the classification of drinking water (Shooler classification) show that overall there is no significant change in the quality of drinking water and only in 2011, reduced quality. Article type: Research Keywords: electrical conductivity, chlorine, dry residue, Schuler, wilcox